Assessment of Microbiological Contamination of Branded and Street Vended Ice-Cream: A Comparative Study in Tangail Municipality, Bangladesh - Afroza Khatun; Md Younus Mia; Masuma Masuma; Kamal Kanta Das (University of Sultan Ageng Tirtayasa, 2023)
Ice cream is a popular dessert consumed by people of all ages, and its consumption can pose a risk of exposure to various microorganisms, including pathogenic bacteria and viruses. Assessment of the microbiological contamination status of branded and street-vended ice cream is crucial to ensure the public health safety. To identify potential sources of contamination, evaluate the effectiveness of the hygiene practices different microbiological and physicochemical analysis was done. Microbial analysis revealed that total viable bacteria in branded ice-cream ranged from 4.8×103 to 1.10×105 cfu/ml and in street vended ice-cream ranged from 7.5×104 to 1.6×108 cfu/ml. Total coliform bacteria present upto 9.20×103 cfu/ml in branded ice-cream and 5.3×103 to 9.6×106 cfu/ml observed in street vended ice-cream. In case of specific pathogen most of the samples contaminated with E. coli and Staphylococcus aureus were found to be present in branded samples up to 104 cfu/ml and 106 cfu/ml on street samples. The pH of both type of ice-cream showed acidic to neutral condition. The range of Total soluble solids in several branded ice-creams were 26 to 29% and the value of TSS obtained in street vended ice-creams were ranging from 5 to 10%. These results indicated that, the microbial quality in all street ice-creams exceeded the BSTI standard and exhibited the lower quality than the industrially produced branded ice-creams due to comparatively faulty manufacturing process and poor hygiene practice.